Forensic Handwriting Investigation Using Digital Photographic Copies of Documents - M. V. Zhizhina (Теория и практика судебной экспертизы, 2020)
The study is a part of the research of the Russian Federal Centre of Forensic Science of the Ministry of Justice of the Russian Federation. It is the initial stage in the development of methodological recommendations for conducting forensic handwriting examinations of images of handwritten objects in digital photocopies of documents. The author has analyzed the current procedural legislation and judicial practice on the use of digital photocopies of documents in proof, as well as the modern expert practice of handwriting studies concerning the images of handwriting realizations presented in such copies. The analysis has shown that these forensic handwriting studies are being quite actively conducted in both judicial and extrajudicial examinations; however, they acquire the procedural status of evidence in the case. Though, the object remains outside the scope of expert methodological support and a comprehensive systematic review in the theoretical aspect. The author considers this practice unacceptable.The article reviews a complex of issues related to determining the properties and attributes of images – handwriting objects presented in photocopies of documents, their qualitative characteristics, and other factors essential for conducting forensic handwriting examinations and formulating relevant conclusions.